Strategi Penerjemahan Idiom Dongeng Anak The Ugly Duckling - Rini Adriati; Grace Jacqulin Burdam (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2023)
This research focuses on translation of idioms in a children's fairy tale with a title of The Ugly Duckling, written by Hans Christian Andersen from Denmark. In this fairy tale there are many interesting idioms to study. However, in the translation process there are challenges faced by the author, namely 1) Idioms do not have a direct equivalent in the target language. 2) Selects the right vocabulary in the target language so that it can be accepted among young readers. The research method in this journal article is a qualitative descriptive research methodology. The results of this study are as follows: produce translations that are commensurate with the source language by using free and communicative translation methods (Newmark, 1988). Even though the grammatical structure of the source text is not the same as the target text, the meaning contained in the target text is commensurate with the source text. Use simple vocabulary in the Target Language that is easy to understand by young age target readers.